Person Recognition via Facial Expression Using ELM Classifier Based CNN Feature Maps - Baloglu, Ulas Baran; Yildirim, Ozal; Ucar, AySegul (Springer International Publishing Ag, 2019)
Extreme learning machine (ELM) and deep learning methods are well-known with their efficiency, accuracy, and speed. In this study, we focus on the application of ELM to a deep learning structure for person recognition with facial expressions. For this purpose, a new convolutional neural network (CNN) model containing Kernel ELM classifiers was constructed. In this model, ELM was not used only as a fully connected layer replacement and energy function was employed to generate feature maps for the ELM. There are two advantages of the proposed model. First, it is fast and successful in face recognition studies. Second, it can drastically improve the performance of a partially-trained CNN model. Consequently, the proposed model is very suitable for CNN models, where the learning process requires a lot of time and computational power. The model is tested with the Grimace data set and experimental results are presented in details.
International Conference on Extreme Learning Machine (ELM) -- OCT 04-07, 2017 -- Yantai, PEOPLES R CHINA
Keywords: Convolutional neural networks; Deep ELM; Extreme learning machine (ELM); Kernel ELM